1999
DOI: 10.1038/sj.cgt.7700069
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin receptor-mediated gene transfer by human epidermal growth factor receptor 2-targeted antibodies and neuregulin-1

Abstract: The human epidermal growth factor receptors 2, 3, and 4 (HER2, HER3, and HER4, respectively) are frequently overexpressed in many human cancers, and therefore may be potential targets for receptor-mediated gene transfer. To evaluate this possibility, we constructed a series of HER-targeted gene transfer vehicles by covalently linking poly-L-lysine polymers (pLYS) to the epidermal growth factor-like domain of the HER ligand neuregulin-1 (NRG1 177-244 ), a HER2 antibody (Ab), and the Fab fragment of the HER2 Ab.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In addition, we have previously reported that ErbB2 is over-expressed in human lung cancers [11], that this over-expression is associated with poor prognosis [12,15], and that targeting this receptor may have therapeutic potential [14,17]. Immunohistochemical analyses of fetal lung tissue localized ErbB2 expression and its associated receptor ErbB3 to the pulmonary epithelium [16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we have previously reported that ErbB2 is over-expressed in human lung cancers [11], that this over-expression is associated with poor prognosis [12,15], and that targeting this receptor may have therapeutic potential [14,17]. Immunohistochemical analyses of fetal lung tissue localized ErbB2 expression and its associated receptor ErbB3 to the pulmonary epithelium [16].…”
Section: Introductionmentioning
confidence: 99%